Bringing science and technology studies into agricultural anthropology: Technology development as cultural encounter between farmers and researchers - Crane, Todd A. (Wiley, 2014)
The “farmer-back-to-farmer” model of agricultural development, pioneered by Robert Rhoades and Robert Booth, urged technologists to use farmers' knowledge and practices as both the starting point for technological innovations as well as the ultimate measure of the value of innovation. This approach was premised upon close ethnographic study of farmers' livelihoods, especially how technical agricultural practices interacted with household dynamics, community structures, and cultural values. However, the original “farmer-back-to-farmer” approach left the “expert” practice of science and technology as an implicitly practical and apolitical space rather than as a subject of ethnographic study. The increasing and diverse articulation of farmers' livelihood practices with the professional practices of agricultural scientists demands theoretical tools that bring them all into the same frame of analysis. This article proposes that the integration of agricultural anthropology and science and technology studies provides a well-balanced toolkit for analyzing participatory technology development as a space of cultural encounter.